Kasta Menjadi Candu Dan Kemanusiaan Yang Terlupakan (Kajian Filosofis) - I Gusti Ngurah Agung Panji Tresna; Kadek Agus Wardana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Caste is a social phenomenon that is familiar to the Balinese Hindu community, becoming a social problem due to the blurring that occurs in the development of the color system into caste. In looking at the socio-cultural phenomenon, the development of a system in society is expected to be inseparable from human values, because if this obfuscation is allowed it will affect the erosion of the moral values of society so that it can affect the character of the community itself. Blurry causes class differences that are not seen from their social function in Balinese Hindu society. The correct appreciation of religious teachings through holy books is deemed not getting a response from the public, and mistakes seem to be deliberately maintained which causes such a blur between the color system and the caste. Mistakes in interpreting the essence and humanity that are interpreted unilaterally by a view that ultimately messes with the value of humanity itself will cause a split that will bring humans to the peak of conflict. Color, in fact, has a purpose not to differentiate one group from another vertically, but to relate to the roles and abilities of each individual. This explains that color is a designation for people who master a certain field. From this concept explains that every color has the opportunity to develop goodness for the sake of lofty ideals, this is the true principle of equality. In fact, humanity with universal Hindu teachings is able to base thoughts on how humans value other humans beyond the attributes that humans can live. Human values must be upheld as an effort to maintain human existence based on the teachings of the Dharma as a manifestation of the creation of a just and civilized human.Key words: caste, color, obfuscation